Pendidikan Kesehatan Perkembangan Identitas Diri Remaja dalam Antisipasi Prilaku Lesbian, Gay, Biseksual dan Transgender di Kelurahan Korong Gadang Kota Padang - Amelia Susanti; Diana Arianti (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2022)
The transition period that adolescents go through from childhood to adulthood is a very important stage. Not all individuals can go through adolescence with positive things and develop into mature, intelligent and critical-minded adults. Some teenagers are actually trapped in negative things such as promiscuity, sexual deviation, drugs, juvenile delinquency, and so on. Sexual deviation is no longer a taboo in society. The large number of gay and lesbian communities has created unrest in the community. One of the efforts that can be done by health workers is in the form of community-based youth mental health promotion. These activities include providing mental health education for adolescents and group therapy activities for adolescents in the Korong Gadang sub-district, Kuranji sub-district, Padang city. The results of the activity showed that there was an effect of health education on the development of adolescent self-identity in anticipating Lesbian, Gay, Bisexual and Transgender behavior on adolescent knowledge. It is hoped that after this activity, adolescent knowledge about reproductive health will increase and can be carried out sustainably by puskesmas nurses who hold adolescent health programs.